The NAC transcription factor family in Eucommia ulmoides: Genome-wide identification, characterization, and network analysis in relation to the rubber biosynthetic genes - Zhang, Shuwen; Xu, Tingting; Ren, Yongyu; Song, Lianjun; Liu, Zhao; Kang, Xiangyang; Li, Yun (Frontiers in Plant Science, 2023)
The NAC transcription factor family is a large plant gene family, participating in plant growth and development, secondary metabolite synthesis, biotic and abiotic stresses responses, and hormone signaling. Eucommia ulmoides is a widely planted economic tree species in China that can produce trans-polyisoprene: Eucommia rubber (Eu-rubber). However, genome-wide identification of the NAC gene family has not been reported in E. ulmoides. In this study, 71 NAC proteins were identified based on genomic database of E. ulmoides. Phylogenetic analysis showed that the EuNAC proteins were distributed in 17 subgroups based on homology with NAC proteins in Arabidopsis, including the E. ulmoides-specific subgroup Eu_NAC. Gene structure analysis suggested that the number of exons varied from 1 to 7, and multitudinous EuNAC genes contained two or three exons. Chromosomal location analysis revealed that the EuNAC genes were unevenly distributed on 16 chromosomes. Three pairs of genes of tandem duplicates genes and 12 segmental duplications were detected, which indicated that segmental duplications may provide the primary driving force of expansion of EuNAC. Prediction of cis-regulatory elements indicated that the EuNAC genes were involved in development, light response, stress response and hormone response. For the gene expression analysis, the expression levels of EuNAC genes in various tissues were quite different. To explore the effect of EuNAC genes on Eu-rubber biosynthesis, a co-expression regulatory network between Eu-rubber biosynthesis genes and EuNAC genes was constructed, which indicated that six EuNAC genes may play an important role in the regulation of Eu-rubber biosynthesis. In addition, this six EuNAC genes expression profiles in E. ulmoides different tissues were consistent with the trend in Eu-rubber content. Quantitative real-time PCR analysis showed that EuNAC genes were responsive to different hormone treatment. These results will provide a useful reference for further studies addressing the functional characteristics of the NAC genes and its potential role in Eu-rubber biosynthesis.